2011
DOI: 10.1007/s00580-010-1154-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of caseous lymphadenitis (CLA) in sheep slaughtered in an abattoir in Tabriz: comparison of bacterial culture and pathological study

Abstract: From January to February 2008, 468 sheep carcasses (335 male and 133 female) in a Khosroshahr (suburb of Tabriz, East Azerbaijan province, Iran) abattoir were randomly selected for inspection. The aim of the study was to estimate the frequency of caseous lymphadenitis (CLA) in sheep and to compare the results of bacterial cultures and histopathology of suspected cases. The mean age of the population was 2.5 years. One hundred ninety-seven cases containing 153 (77.7%) males and 44 (22.3%) females had prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
2
18
2
Order By: Relevance
“…Abscess formation in cut sections of lungs and liver due to C. pseudotuberculosis in alpaca has been reported (Braga et al, 2006;Fontaine and Baird, 2007). Previous studies have disclosed that presence of small tubercles packed with caseous material in lungs, liver, internal lymph nodes and mesenteric lymph nodes are the characteristic features of visceral forms of caseous lymphadenitis caused due to C. pseudotuberculosis (Yeruham et al, 2003;Zavoshti et al, 2012;Chikhaoui and Khoudja, 2013). Different studies have also reported similar pathological lesions in infected animals (Pratt et al, 2005;Quino de Sa et al, 2013;Chikhaoui and Khoudja, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abscess formation in cut sections of lungs and liver due to C. pseudotuberculosis in alpaca has been reported (Braga et al, 2006;Fontaine and Baird, 2007). Previous studies have disclosed that presence of small tubercles packed with caseous material in lungs, liver, internal lymph nodes and mesenteric lymph nodes are the characteristic features of visceral forms of caseous lymphadenitis caused due to C. pseudotuberculosis (Yeruham et al, 2003;Zavoshti et al, 2012;Chikhaoui and Khoudja, 2013). Different studies have also reported similar pathological lesions in infected animals (Pratt et al, 2005;Quino de Sa et al, 2013;Chikhaoui and Khoudja, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Initially these lymph nodes are filled with serous fluid which later on is converted to pus filled tubercles. The disease also causes lesions in other visceral organs including liver, lungs and spleen (Zavoshti et al, 2012). C. pseudotuberculosis biovar ovis induces diffused swellings in brisket regions, skin of fore limbs and hind quarter in exposed animals (Moussa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are non-fatal chronic or subclinical with high morbidity rate and frequent relapses [4,9,13]. MD is mainly encountered in young animals within the first 4-10 months of life [32], while CLA is mainly in adult animals and is found increasing with age [33]. Unlike CLA, MD was found associated with fattening; incidence was found to be higher in feedlot areas (62.5%) compared to natural grazing areas (5.8%) [34].…”
Section: Nature Risk Factors Prevalence and Economic Impactmentioning
confidence: 99%
“…Similarly, the CLA prevalence in sheep was found as 42.4% in a study conducted in the western United States (10), and 12.6% from bacteriological analysis and 20.08% from histopathological analysis in Tabriz (Iran). While the frequencies of CLA observation in sheep and goats were 23.33% and 11.04%, respectively, according to clinical examination, these frequencies were reduced by 22.10% and 7.77% in sheep and goats, respectively, if the agent was determined through bacteriological methods (11). CLA positivity in sheep was identified as 71% in a study using an indirect ELISA method in Brazil (9).…”
mentioning
confidence: 99%